Radical Reform in Irish Schools, 1900-1922 - O'Doherty, Teresa. author. aut Link
VII, 307 p. 1 illus.
Keywords: “Timely, original and scholarly, this book is compulsory reading for anyone interested in the history of education in Ireland and the history of modern Ireland more broadly. The compelling narrative questions various invented traditions in Irish education in the period 1900-1922, shining a spotlight on the life and work of William Starkie, Resident Commissioner for National Education in the period 1899-1920. The book contributes significantly to the body of scholarship on the growth of child-centred education internationally and examines the reforms of Irish schooling during the early decades of the 20th century.” -Judith Harford, Professor of Education, University College Dublin, Ireland. This book examines the radical reform that occurred during the final two decades of British rule in Ireland when William Starkie (1860–1920) presided as Resident Commissioner for the Board. Following the lead of industrialized nations, Irish members of parliament sought to encourage the establishment of a state-funded school system during the early nineteenth century. The year 1831 saw the creation of the Irish National School System. Central to its workings was the National Board of Education which had the responsibility for distributing government funds to aid in the building of schools, the payment of inspectors and teachers, the publication of textbooks, and the cost of teacher training. In the midst of radical political and cultural change within Ireland, visionaries and leaders like Starkie filled an indispensable role in Irish education. They oversaw the introduction of a radical child-centered primary school curriculum, often referred to as the ‘new education’. Filling a gap in Irish history, this book provides a much needed overview of the changes that occurred in primary education during the 22 years leading up to Ireland’s independence. Teresa O’Doherty is President of the Marino Institute for Education and Adjunct Professor at Trinity College Dublin. Having been a teacher, educator, and scholar for over twenty years, her research revolves around teacher education and the history of education. Together with Tom O’Donoghue, Teresa published the book, Irish Speakers and Schooling in the Gaeltacht, 1900 to the Present (Palgrave) in 2019. Tom O’Donoghue is Professor of Education in the Graduate School of Education at The University of Western Australia, Australia, and Elected Fellow of the Australian Academy of the Social Sciences and the Royal Historical Society, UK. In 2021, he is also Full Visiting professor at the University College Dublin. He co-authored Irish Speakers and Schooling in the Gaeltacht, 1900 to the Present with Teresa O’Doherty.